ANALISIS NILAI TAMBAH KEDELAI (Glycine max L.) MENJADI TAHU PADA INDUSTRI TAHU BINTANG - Freddy Halomoan Siburian; Dina Lesmana (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
Soybean is one of the agricultural products that is used by some residents, especially Lempake Village, which is processed into tofu and tempeh in order to obtain a higher selling price in the market. Soybean processing activities into tofu and tempeh can change the form of primary products into new products with higher economic value after going through the production process, so they can provide added value. The aims of this study were 1) to determine the amount of income and the R/C ratio of the Tofu Bintang Industry in Lempake Village and 2) to analyze the amount of added value of soybeans in the Tofu Bintang Industry in Lempake Village. This research was conducted in the Tofu Bintang Industry from December 2022 to January 2023. The sampling method was carried out using a purposive sampling method with the respondent being the owner of the Tofu Bintang Industry. Data collection was carried out by observing and interviewing respondents. Methods of data analysis used quantitative and qualitative analysis and added value using the Hayami method. The results showed that the production costs incurred for one month of production in the Tofu Bintang Industry amounted to Rp. 171,561,012, receipts of Rp. 239,025,200, the revenue of Rp. 67,464,188 and an R/C Ratio of 1.39. The added value generated for small tofu was 7,677/kg with an added value ratio of 34.89%, and for large tofu was Rp. 7,066 / kg with a value-added ratio of 32.11%. The conclusion of this study was that the Tofu Bintang Industry was feasible because the R/C ratio was more than 1, which means that the Tofu Bintang Industry earns profits and was feasible to cultivate.